Longitudinal blood pressure and cardiovascular outcomes in heart failure: An individual patient data pooling analysis of clinical trials - Li, Jing-Wei; Wang, Jiang; Chen, Yunlong; Yang, Hao; Wang, Yi; Wang, Xia; Xiao, Jingjng; Wang, Ying; Qian, Dehui; Yu, Shiyong; Zhao, Xiaohui; Tan, Hu; et al. (European journal of heart failure, 2025)
Previous analyses of the relationship between blood pressure (BP) and heart failure (HF) outcomes have primarily used baseline values rather than longitudinal measurements. We aimed to elucidate associations between longitudinal BP and clinical outcomes in patients with HF with reduced ejection fraction (HFrEF), mildly reduced ejection fraction (HFmrEF), and preserved ejection fraction (HFpEF). We conducted a comprehensive analysis of 28 406 patients from eight trials, evaluating time-dependent BP categorized by tertiles and per 10 mmHg increments in BP on outcomes. The primary endpoint was the time to the first occurrence of a composite endpoint comprising cardiovascular death or HF hospitalization. Multivariate Cox regression analysis revealed a J-shaped relationship between BP and the composite outcome in HFrEF. Specifically, compared with the middle-level systolic BP (SBP), low SBP was associated with a higher risk of the composite endpoint (hazard ratio [HR] 1.71, 95% confidence interval [CI] 1.60-1.82; p < 0.001) and high SBP showed a non-significant change in risk (HR 1.07, 95% CI 0.97-1.18; p = 0.187). Conversely, a U-shaped relationship was observed in HFmrEF and HFpEF. Low SBP was linked to a higher risk of the composite endpoint (HR 1.74, 95% CI 1.47-2.07; p < 0.001), and high SBP similarly increased the risk (HR 1.77, 95% CI 1.45-2.17; p < 0.001). The relationship between BP and HF outcomes is non-linear and closely tied to left ventricular ejection fraction. Low SBP consistently predicts a poor prognosis, whereas high SBP is associated with an increased risk in HFmrEF and HFpEF but not in HFrEF.